Adenosine 2A Receptor Antagonist Prevented and Reversed Liver Fibrosis in a Mouse Model of Ethanol-Exacerbated Liver Fibrosis - Chiang, Dian J. (Public Library of Science, 2013)
The effect of moderate alcohol consumption on liver fibrosis is not well understood, but evidence suggests that adenosine may play a role in mediating the effects of moderate ethanol on tissue injury. Ethanol increases the concentration of adenosine in the liver. Adenosine 2A receptor (A2AR) activation is known to enhance hepatic stellate cell (HSC) activation and A2AR deficient mice are protected from fibrosis in mice. Making use of a novel mouse model of moderate ethanol consumption in which female C57BL/6J mice were allowed continued access to 2% (vol/vol) ethanol (11% calories) or pair-fed control diets for 2 days, 2 weeks or 5 weeks and superimposed with exposure to CCl(4), we tested the hypothesis that moderate ethanol consumption increases fibrosis in response to carbon tetrachloride (CCl(4)) and that treatment of mice with an A2AR antagonist prevents and/or reverses this ethanol-induced increase in liver fibrosis. Neither the expression or activity of CYP2E1, required for bio-activation of CCl(4), nor AST and ALT activity in the plasma were affected by ethanol, indicating that moderate ethanol did not increase the direct hepatotoxicity of CCl(4). However, ethanol feeding enhanced HSC activation and exacerbated liver fibrosis upon exposure to CCl(4.) This was associated with an increased sinusoidal angiogenic response in the liver. Treatment with A2AR antagonist both prevented and reversed the ability of ethanol to exacerbate liver fibrosis. CONCLUSION: Moderate ethanol consumption exacerbates hepatic fibrosis upon exposure to CCl(4). A2AR antagonism may be a potential pharmaceutical intervention to decrease hepatic fibrosis in response to ethanol.